Growing vegetable soup - Ehlert, Lois. (San Diego : Harcourt Brace & Co., 1987)
A father and child grow vegetables and then make them into a soup.
360L
Decoding demand: 45 (medium) Semantic demand: 46 (medium) Syntactic demand: 36 (low) Structure demand: 66 (high)
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Vegetable gardening; Soups; Fiction; Fiction